Genetic Origins and Movement of Lake Sturgeon Acipenser Fulvescens in the St. Louis River and Western Lake Superior - Estep, Kayden R. (University of Wisconsin-Stevens Point, College of Natural Resources, 2019)
Lake Sturgeon Acipenser fulvescens were extirpated from the St. Louis River (SLR) by the early 1900’s due to overfishing and habitat degradation. With the passing of the Clean Water Act and improvements to water quality, a stocking program was initiated in 1983 by the Minnesota Department of Natural Resources, Wisconsin Department of Natural Resources, and Fond Du Lac Band of Lake Superior Chippewa to reintroduce Lake Sturgeon to the SLR. Most stocked Lake Sturgeon were obtained from the Wolf River (Lake Winnebago) genetic stock and some (much fewer than the Wolf River) were obtained from the Sturgeon River (Lake Superior) genetic stock. Stocking continued almost yearly until 2000. Recently, spawning and natural recruitment has been documented near the Fond Du Lac Dam, the upstream limit for Lake Sturgeon migrating from Lake Superior. However, it was unknown if the Lake Sturgeon spawning in the SLR were from stocking events or strays from other areas of Lake Superior. Additionally, it is unknown if Lake Sturgeon in the SLR represent a resident population or if they exhibit a migratory life history; movements of Lake Sturgeon in and out of the SLR is unknown and represents a knowledge gap hindering effective management of this population. My objectives were to determine (1) the genetic origins of Lake Sturgeon Spawning in the SLR, (2) if the timing, frequency, and magnitude of Lake Sturgeon migrations between the SLR and Lake Superior were related to genetic strain, physical characteristics (sex, size) or environmental conditions (temperature, discharge) and (3) if spawning locations were influenced by genetic stock, individual demographic characteristics, environmental conditions, and restored habitats. Most Lake Sturgeon captured (79%) genetically assigned to the Wolf River genetic stock (Lake Winnebago) with greater than 80% probability. Other genetic stocks present included the Pic River and Goulais River. The SLR Sturgeon population was found to be an open population with fish exhibiting both migratory and resident life histories. Over the course of the study 78 of 137 acoustically tagged Lake Sturgeon emigrated from the SLR to Lake Superior and nearly half of these fish were detected on U.S. Fish and Wildlife acoustic receivers between Bark Point and Chequamegon Bay, WI. Emigration peaked in June of each year but was not related to genetic strain or physical characteristics. Water temperature was a significant predictor of emigration and it is possible SLR Lake Sturgeon use Lake Superior for thermal refuge. Egg mats set in 2018 captured no Lake Sturgeon eggs and Sturgeon were only observed spawning immediately below the Fond Du Lac Dam. Spawning area does not appear to be limited in the SLR. Furthermore, the restoration stocking effort of Lake Sturgeon into the SLR appears to have been successful. The stocking of Wolf River strain Sturgeon appears to have been successful, and it is possible that the stocking of Sturgeon River fish was also successful although none of the genotyped samples genetically assigned to the Sturgeon River population. The presence of Lake Sturgeon strays coupled with the open population of the SLR and observed movement of SLR Sturgeon to other areas of Lake Superior highlights the importance of interjurisdictional management of Lake Superior Lake Sturgeon populations. My results indicate that the Lake Sturgeon fishery in the Wisconsin waters of Lake Superior is likely a mixed stock fishery. However, harvest of Lake Sturgeon in these waters is likely counter-productive to the restoration of the female-limited SLR population, especially if minimum length limits increased as proposed. Within the SLR, sampling of the population during the spring spawning period should continue at the current level of effort to allow for estimation of abundance and better knowledge of population dynamics and demographics. The acoustic array should be maintained through 2028 to inform spawning periodicity and examine the various life history strategies of SLR Lake Sturgeon. Genetic assessment of the spawning population should continue as the genetic composition of the spawning population may change as more stocked fish become sexually mature and due to the spawning periodicity exhibited by Lake Sturgeon. The stocking of the SLR is potentially scheduled to recommence in 2019 and should be viewed as an important opportunity to learn more about the juvenile life stage of Lake Sturgeon in the SLR as well as other life history and population attributes (e.g., age and growth). Overall, the SLR Sturgeon population appears to be headed towards recovery. Adaptive management practices currently being employed and should be continued to help guide the further recovery of this population.